Single-photon excitation of K α in heliumlike Kr34+: results supporting quantum electrodynamics predictions - Epp, Sascha W.; Steinbrügge, René; Bernitt, Sven; Rudolph, J. K.; Beilmann, Christian; Bekker, H.; Müller, A.; Versolato, O. O.; Wille, H.-C.; Yavaş, H.; Ullrich, J.; Crespo López-Urrutia, José Ramon (Physical review. A, Atomic, molecular, and optical physics, 2015)
We study two fundamental transitions from the ground state 1S0 to 1P1 (w line) and 3P1 (y line) in heliumlike Kr34+ by resonant single-photon excitation using an electron-beam ion trap and monochromatic x rays at PETRA III. Our results for the transition energies E(w)=13114.47(14) eV and E(y)=13026.15(14) eV are in excellent agreement with quantum electrodynamics calculations, but disagree for w with the average of the hitherto reported experimental results ELit(w)=13115.15(17) eV. Independently of any energy calibration, we obtain a value E(w)/E(y)=1.006780(7), also in consistency with predictions.
Im Titel ist "34+" hochgestellt
Gesehen am 16.07.2020